Deformaciones isométricas infinitesimales de superficies multidimensionales ensambladas - Pavel Markov; Olman Trejos (Revista de Matemática: Teoría y Aplicaciones, 2012)
The article introduces the concept of multidimensional pasted surfaces and considers the case of different dimensions in the surfaces to be pasted. Infinitesimal deformations of such surfaces are also considered. In a general way, it is proved that, if the surface pieces have first order infinitesimal rigidity, then the pasted surface contains infinitesimal rigidity of first order.